Fire and edge disturbances in the Amazon rainforest: impacts on animal–fruit and seed interactions - Jefferson Bruno B. S. Oliveira; Wesley Dáttilo; Hernani F. M. Oliveira; Paulo M. Brando; Walter S. de Araújo; Mathias M. Pires; Lucas N. Paolucci (Oecologia, 2026)
Burned forests—particularly at their edges—are expected to lose capacity for regeneration, and subsequent disturbances may further limit it. Animal–plant interactions are critical to the resilience of tropical forests to disturbances, as they sustain key ecological functions. However, climate and land-use changes are intensifying fire regimes, potentially disrupting these interactions. Using experimental approaches with artificial fruits (in the understory and on the terrestrial level) and agricultural crop seeds (accessed by all fauna and invertebrates-only), we investigated how animal–plant interactions, focusing on key faunal groups, are affected in disturbed forests 12 years after repeated experimental fires and under continuous edge effects in the southeastern Brazilian Amazon. We found that understory animal–fruit interactions were similar across burned, edge, and undisturbed forests, whereas terrestrial animal–fruit interactions were twice as high at the unburned edge. While vertebrates accessed understory fruits more frequently, invertebrates dominated terrestrial interactions, highlighting their complementary roles. In contrast, seed interactions by both the broader faunal community and invertebrates-only declined in the interior and edge of burned forests, while invertebrate-driven seed interactions were similar between unburned edge and burned forest interior. Our findings show contrasting responses to indirect fire and edge effects across ecological interactions that support forest regeneration. Therefore, we underscore the fragility of ecological interactions through faunal access to reproductive vegetation diaspores: while animal–fruit interactions were resilient in burned forests and edges, secondary animal–seed interactions were impacted by fire. These results suggest that disturbed forests may require more than a decade to recover their interactions fully.